Pengaruh Rasio Kemandirian Daerah, Efektifitas Pendapatan Asli Daerah, dan Pengelolaan Belanja Daerah terhadap Kinerja Keuangan Daerah Pada Pemerintah Kabupaten/Kota di Provinsi Sumatera Selatan - Yeyen Yeyen; Kartika Rachma Sari; Choiruddin Choiruddin (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2025)
This study aims to determine the effect of the Regional Independence Ratio, the Effectiveness of Regional Original Income, and Regional Expenditure Management on Regional Financial Performance in Regency/City Governments in South Sumatra Province. The population used in this study were all Regencies and Cities in South Sumatra Province consisting of 13 Regencies and 4 Cities starting from the 2018 to 2023 Budget Period. This study is a quantitative study using secondary data obtained from the official website of the Audit Board of Indonesia (www.BPK.go.id). This study was analyzed by multiple linear regression using Eviews 12 Software. The results of this study indicate that the Regional Independence Ratio, the Effectiveness of Regional Original Income, and Regional Expenditure Management have an effect on Regional Financial Performance.